Specific, rapid synthesis of Phe-RNA by RNA - Illangasekare, Mali (The National Academy of Sciences, 1999)
RNA 77, derived by selection amplification, accelerates its own conversion to Phe-RNA (relative to randomized RNA) more than 6 × 10(7)-fold, by using amino acid adenylates as substrate. A modified assay system allows measurement of slow rates of aa-RNA formation, which for disfavored amino acid substrates can be more than 10(4)-fold slower than phenylalanine. Thus unlike previously characterized self-aminoacylators, RNA 77 catalysis is highly amino acid selective. Remarkably, both rates of aminoacyl transfer and amino acid specificities are greater for RNA 77 than measured for protein PheRS. These data experimentally support the possible existence of an ancestral amino acid-specific translation system relying entirely on RNA catalysis. RNA 77 itself embodies a possible transitional evolutionary state, in which side-chain-specific aa-RNA formation and anticodon-codon pairing were invested in the same molecule.